RADISH CV. MOKHOVSKIY IS A SOURCE OF MS- AND MF-LINES AT BREEDING FOR HETEROSIS - M. I. Fedorova; T. V. Zayachkovskaya; E. A. Domblides; A. S. Domblides (Овощи России)
Based on hybrid and inbreed population of radish cv. Mokhovskiy using CMS-ogura nine lines with 100% of male sterility and fertile maintainers were selected. Using the multiplex PCR, the presence of cytoplasm of Ogura type in ms-lines and its absence in mf-lines were confirmed.